Portuguese edition of the Compendium of key human rights documents of the African Union - Magnus Killander; Christof Heyns (Pretoria University Law Press (PULP), 2008)
Portuguese edition of the Compendium of key human rights documents of the African Union Edited by Christof Heyns & Magnus Killander 2008 ISBN: 978-0-9814124-2-9 Pages: viii 325 Print version: Available Electronic version: Free PDF available
Portuguese